Delayed seizures in bupropion overdose with concomitant ingestion of alpha-2 agonist: a case report. Issue 1 (1st January 2017) - Liss, David B.; Phillips, Todd M.; Pizon, Anthony F.; Schwarz, Evan S.
ABSTRACT: Clonidine and guanfacine are common alpha-2 adrenergic receptor agonists that can cause decreased sympathetic tone. Patients who overdose on bupropion, norepinephrine, and dopamine reuptake inhibitor may present with signs or symptoms of adrenergic excess including tachycardia, tremor, and agitation or more severe effects such as cardiac dysrhythmia and seizure. These pharmacological effects appear to oppose each other. The outcomes of patients with concomitant overdoses of bupropion and alpha-2 agonists are not well described. We present the cases of two adolescent patients, a 16-year-old male, and a 17-year-old female, who overdosed on bupropion and either clonidine or guanfacine. Both patients had relatively minor symptoms until 20.5 (Case 1) and 23 (Case 2) hours when they had multiple seizures. The patient in Case 1 did not survive. Bupropion overdose may cause delayed toxicity including seizures. This fact can present a clinical dilemma to the treating physician asked to medically clear a patient for psychiatric admission. Symptoms that predict seizure are not reliable in these cases and can be further masked by concomitant alpha-2 agonist overdose. We believe that these two bupropion overdose patients had delayed seizures with minimal prodromal symptoms possibly due to the masking effect of concurrent alpha-2 agonist ingestion.